ANALISIS PERBANDINGAN AKURASI PENGUKURAN SUHU TUBUH MENGGUNAKAN SENSOR LM35 DAN MLX90614 - Dewi Arofah; Khoerul Anwar; Sigit Setyowibowo (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2025)
The COVID-19 pandemic has increased the need for accurate body temperature measurement in public facilities. This study aimed to compare the accuracy of two types of temperature sensors, the LM35 and the MLX90614, for measuring human body temperature. Tests were conducted 36 times on adults, with a manufactured thermogun as the primary comparator. The results showed a significant difference in accuracy: LM35 sensor: Has an average error of 15.62% with an accuracy of 84.38%. This sensor operates based on linear voltage changes through direct contact with an object.MLX90614 sensor: Has an average error of only 1.17% with a high accuracy of 98.83%. The advantage of the MLX90614 lies in its ability to capture infrared light without physical contact, supported by a low-noise amplifier, 17-bit ADC, and the MLX90302 DSP unit, which the LM35 lacks. The conclusion is that the MLX90614 is far more effective and accurate for monitoring human body temperature.